Integrating Kearifan Lokal (Local Wisdom) with Climate Adaptation Strategies: A Participatory Action Research on Enhancing Community Resilience and Achieving SDG 13 in Indonesia's Coastal Communities - Jasmila Tanjung; Caelin Damayanti; Neva Dian Permana; Andi Fatihah Syahrir; Hesti Putri; Aman Suparman; Susi Diana (HM Publisher, 2025)
Coastal communities in Indonesia face existential threats from climate change. Conventional top-down adaptation strategies often fail due to a disconnect from local socio-ecological realities, overlooking a critical resource: traditional ecological knowledge, or kearifan lokal. This study investigates a knowledge co-production model that synergizes kearifan lokal with modern climate science to build community resilience. We employed a 24-month, mixed-methods Participatory Action Research (PAR) design in three highly exposed coastal villages in North Java, Indonesia. Ethical protocols, including Free, Prior, and Informed Consent (FPIC), were foundational. Qualitative data were gathered from in-depth interviews (n=30), focus groups (n=12), and ethnographic observation. Quantitative data came from a pre-test/post-test household survey (n=450) measuring a validated, multi-dimensional Community Resilience Index (CRI). Interventions were co-designed, blending traditional practices like the pranata mangsa (ethno-astronomical calendar) and the wana tirta (mangrove philosophy) with scientific recommendations. A linear mixed-effects model was used to analyze changes in CRI scores. The co-designed strategies led to a statistically significant increase in the mean CRI from a baseline of 2.8 (SD=0.65) to 4.2 (SD=0.48) post-intervention (p<0.001). Significant improvements were observed across all resilience dimensions, most notably in Economic Capital (+59.1%) and Adaptive Capacity & Governance (+51.7%). The revitalization of practices such as the restoration of 50 hectares of mangroves, guided by both wana tirta principles and scientific species selection, enhanced coastal protection and local livelihoods. In conclusion, the co-production of knowledge, facilitated through a PAR framework, is a potent mechanism for building effective, culturally embedded, and sustainable climate resilience. This model empowers communities as active agents in their adaptation journey and offers a scalable, evidence-based pathway for achieving SDG 13 in Indonesia and other climate-vulnerable nations.